UTILIZATION OF ASSET BUILDING AND LAND EKS BAKORWIL FOR HOSPITALS IN PATI, PEKALONGAN, AND MAGELANG AREA - S. Budi Prasetyo; Arif Sofianto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2017)
The purpose of this study is to: 1) analyze the condition of ex-Bakorwil assets in Pati, Pekalongan, and Magelang areas from the management side, the condition of the building, infrastructure and environment, 2) analysis of possible assets of ex-Bakorwil in Pati Regency, Pekalongan City, and Magelang City to be used as a hospital, as well as necessary steps. Data in this study were collected through interviews, discussions, and direct observation of the study object. The data analysis in this study uses qualitative techniques with interactive models developed by Miles and Huberman. The conclusions of this study are: 1) the possible asset for the establishment of the new hospital is the official house in Pati and Pekalongan, but the location that need new hospital is Magelang and Pekalongan, for the existing Pati there are Kelet Hospital, Jepara; 2) the establishment of hospitals in Pekalongan utilize the assets of former official houses, while in Magelang need to look for alternative assets; 3) The hospital to be established is directed to the center of excellence that is for Pekalongan is Mother and Child hospital, for Magelang is Cancer hospital.